Polyextracts of medicinal plants vs bacteria associated with acute respiratory infections (IRAS) - Mayo Tadeo, Rosa Iris; Espinoza Rojo, Mónica; Jiménez Hernández, Javier; Godinez Jaimes, Flaviano; Damián Nava, Agustín; Vargas Alvarez, Dolores (Revista Mexicana de Ciencias Agrícolas, 2020)
The objective of this research work was to model the preparation of a syrup formulation based on plant extracts of bougainvillea, eucalyptus, cinnamon, marigold and itamo to inhibit the growth of S. aureus and S. pyogenes, bacteria associated with respiratory infections. The presence of secondary metabolites in the methanolic extracts of each species was determined by chromatography, as well as the antibacterial activity of the extracts and syrups and their antioxidant capacity were evaluated. Eucalyptus extract was found, to be the best at inhibiting bacteria, just like its syrup form, and cinnamon extract is the best antioxidant.
Keywords: antibacterial activity; antioxidant activity; plant extracts; secondary metabolites